Divide 2x^3 + 9x^2 + 5 by x^2 + 4x - 3. Find the quotient and remainder

(2x^3 + 9x^2 + 5)/(x^2 + 4x - 3) = (2x^3/x^2 + 4x - 3) + (9x^2/x^2 + 4x - 3) + (5/x^2 + 4x - 3) = x^2 + 4x - 3 R 2x + 8

Question

Asked 7/18/2013 4:27:55 PM

Updated 10/29/2014 4:04:14 AM

1 Answer/Comment

Edited by andrewpallarca [10/29/2014 4:04:13 AM]

Rating

3

(2x^3 + 9x^2 + 5)/(x^2 + 4x - 3)

= (2x^3/x^2 + 4x - 3) + (9x^2/x^2 + 4x - 3) + (5/x^2 + 4x - 3)

= x^2 + 4x - 3 R 2x + 8

= (2x^3/x^2 + 4x - 3) + (9x^2/x^2 + 4x - 3) + (5/x^2 + 4x - 3)

= x^2 + 4x - 3 R 2x + 8

Added 10/29/2014 4:04:14 AM

This answer has been confirmed as correct and helpful.

27,102,325

questions answered

There are no comments.